2017
DOI: 10.1111/ldrp.12134
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of an Intervention to Promote Inference Generation by Adolescent Poor Comprehenders

Abstract: This brief experimental study investigated the initial promise of an intervention designed to promote inference generation in adolescents with reading comprehension difficulties. The intervention, provided for nine sessions, included multisyllable word study, teacher explanation and modeling of inference generation and other comprehension processes, and having students practice by thinking aloud about text. Research questions addressed proximal effects on measures of the intermediate goals of the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
0
13
0
2
Order By: Relevance
“…Barth and Elleman (2017) reported that middle grades struggling readers who received an intervention designed to simultaneously build content knowledge and teach multiple inference generation strategies made significant gains relative to a business-as-usual comparison group on a proximal measure of content knowledge and on a standardized measure of general reading comprehension. Denton et al (2017) found that ninth-graders with reading comprehension difficulties randomly assigned to a nine-session inference instruction intervention that included multisyllable word study, explicit instruction in inference generation, and guided practice in thinking aloud about text made moderate but nonsignificant gains relative to students in a business-as-usual comparison condition on proximal measures of inference skill. There has been no study that has investigated the effects of an inference instruction intervention on the inferential and general reading comprehension of students with reading comprehension difficulties who are ELs.…”
Section: Inference Instruction For Students With Reading Comprehensiomentioning
confidence: 96%
“…Barth and Elleman (2017) reported that middle grades struggling readers who received an intervention designed to simultaneously build content knowledge and teach multiple inference generation strategies made significant gains relative to a business-as-usual comparison group on a proximal measure of content knowledge and on a standardized measure of general reading comprehension. Denton et al (2017) found that ninth-graders with reading comprehension difficulties randomly assigned to a nine-session inference instruction intervention that included multisyllable word study, explicit instruction in inference generation, and guided practice in thinking aloud about text made moderate but nonsignificant gains relative to students in a business-as-usual comparison condition on proximal measures of inference skill. There has been no study that has investigated the effects of an inference instruction intervention on the inferential and general reading comprehension of students with reading comprehension difficulties who are ELs.…”
Section: Inference Instruction For Students With Reading Comprehensiomentioning
confidence: 96%
“…Moderation analyses permit investigations of differential intervention effects. Although prior reading intervention work across grade levels has investigated moderating effects of variables such as intervention fidelity and quality (Boardman et al, 2016), implementation by teachers versus paraeducators (Vadasy & Sanders, 2009), English-learner status (Vaughn, Martinez, & Wanzek, 2017), and ethnicity (Denton et al, 2017), investigations of the moderating effects of pretest reading skills on intervention effects in middle and secondary school have been infrequent. Lang et al (2009) contrasted four intensive interventions for struggling readers in high school and found that interventions were differentially effective for students based on their level of reading risk.…”
Section: Multicomponent Interventions May Be More or Less Beneficial mentioning
confidence: 99%
“…This reduced, poorly-connected text representation impairs the ability of PC to recall text ideas, particularly well-connected central ones, and answer comprehension questions, particularly integrative and inferential ones, after reading. Previous intervention studies, which have trained PC on the employment of high-level strategies during reading, have shown an improvement in poor comprehenders' text comprehension and memory (Brown, Palincsar, & Armbruster, 1984;Denton, York, Francis, Haring, Ahmed, & Bidulescu, 2017;Mcgee & Johnson, 2003;Ray & Meyer, 2011;Yuill & Joscelyne, 1988;Yuill & Oakhill, 1988). Similar intervention studies should further examine the effect of high-level strategies, especially the generation of connective inferences, on the remedy of centrality deficit in PC.…”
Section: The Effect Of Online Processing On Offline Performance By Poor Comprehendersmentioning
confidence: 93%